Mesenchymal stem cell therapy for retro-corneal membrane - A clinical challenge in full-thickness transplantation of biosynthetic corneal equivalents - Rajendran, Vijayalakshmi; Netuková, Magdalena; Griffith, May; Forrester, John V; Kuffová, Lucia (Acta biomaterialia, 2017)
UNLABELLED: Artificial corneas (keratoprostheses) and biosynthetic collagen-based corneal equivalents are surgical implants designed to ease the global burden of corneal blindness. However, keratoprostheses in many cases fail due to development of fibrous retro-corneal membranes (RCM). Fibrous membranes which develop in the anterior chamber after prosthesis implantation do so on a matrix of fibrin. This study investigated fibrin deposition and RCM formation after full-thickness collagen-based hydrogel implants and compared them with syngeneic and allogeneic corneal grafts in mice. Fibrin cleared from the anterior chamber within 14 days in both allo- and syn-grafts but, persisted in hydrogel implants and developed into dense retro-corneal membrane (RCM) which were heavily infiltrated by activated myofibroblasts. In contrast, the number of CD11b+ macrophages infiltrating the initial deposition of fibrin in the anterior chamber (AC) after hydrogel implantation was markedly reduced compared to syn- and allo-grafts. Inoculation of mesenchymal stem cells prior to collagen gel implant promoted clearance of gel-associated fibrin from the anterior chamber. We propose that a failure of macrophage-mediated clearance of fibrin may be the cause of RCM formation after collagen-based hydrogel implants and that mesenchymal stem cell therapy promotes clearance of fibrin and prevents RCM formation. STATEMENT OF SIGNIFICANCE: The manuscript addresses the potential value of bone marrow-derived mesenchymal stem cell therapy for retro-corneal membrane (RCM) formation in full-thickness transplantation of biosynthetic corneal equivalents. This work reports the pathophysiological changes in the anterior chamber of the mouse eye following full-thickness recombinant human cross-linked collagen-based hydrogel implants in which persistent fibrin promotes the development of dense RCM. Furthermore, pre-treatment with mesenchymal stem cells reduces RCM formation and enhances corneal transparency.
Keywords: Fibrin; Mice, Inbred BALB C; nemoci rohovky; Transplantation, Isogeneic; myši transgenní; hydrogely; rohovka; Mesenchymal stem cells; Mice; Mesenchymal Stem Cells; bioprotézy; Retro-corneal membrane; mezenchymální kmenové buňky; Allografts; ženské pohlaví; zvířata; Bioprosthesis; Hydrogels; membrány umělé; myši inbrední BALB C; transplantace izogenní; Full-thickness collagen-based hydrogel implants; myši; alografty; Membranes, Artificial; Corneal Diseases; Female; Mice, Transgenic; Cornea; Animals